A new parameterization of photolysis rates for oxygenated volatile organic compounds (OVOCs) - Y. Peng; B. Yuan; S. Wang; X. Song; Z. Peng; W. Wang; S. Yang; J. Qi; X. He; Y. Huangfu; X.-B. Li; M. Shao (Atmospheric Chemistry and Physics)
Oxygenated volatile organic compounds (OVOCs) play a crucial role in atmospheric chemistry, significantly influencing radical production and VOC degradation through photolysis. However, current research on OVOC photolysis is limited by insufficient species coverage in the mechanisms and incomplete understanding from a species-specific perspective. In this study, the photolysis frequencies of 109 OVOCs were compiled into a comprehensive photolysis dataset. Based on their molecular structures, a parameterization for the photolysis frequencies of carbon- and nitrogen-containing OVOCs was developed. By establishing a relationship between species structure and photolysis frequency, this approach avoids the limitation of insufficient quantum yield data, enabling the estimation of photolysis rate constants for compounds lacking experimental measurements. Photolysis frequencies for the dataset species were successfully reproduced with 21 reference values and 10 adjustment coefficients. Using an automated program based on this method, photolysis rate constants for 3039 OVOCs were predicted, and the Master Chemical Mechanism (MCM) v3.3.1 chemical mechanism was updated and expanded to include photolysis for 714 additional species. The introduction of the new photolysis mechanism has altered both the concentrations of photodegradable OVOCs and the relative proportions of their removal pathways. Non-HCHO OVOCs, particularly multifunctional species with carbonyl groups, contribute significantly to ROx radical production. At three different sites, non-HCHO OVOC photolysis accounts for 25 %–45 % of ROx production, surpassing HCHO photolysis. The importance of oxidation products from aromatics and alkenes is highlighted, offering new insights into OVOC photolysis from a species-specific perspective.